Exploring Leadership Styles and Their Impact on Innovation in TVET: Insights from a Systematic Analysis - Roswina Dianawati; Lorencia Endah Cahya Ningrum; Syamsul Hadi; Didik Nurhadi; Widiyanti Widiyanti; Yuli Sutoto (IJORER : International Journal of Recent Educational Research, 2025)
Objective: This study examines the influence of leadership styles on promoting innovation in the Technical and Vocational Education and Training (TVET) sector. The study addresses a notable research gap by identifying the leadership strategies that are most effective in fostering innovation within the swiftly changing educational and industrial environments. Method: The study used a Systematic Literature Review (SLR) technique organized by PRISMA criteria. Articles from peer-reviewed journals in the Scopus and ERIC databases, published between 2021 and 2024, were examined. A thorough search technique included specified keywords and Boolean operators, resulting in 659 articles, of which 36 were chosen following rigorous screening according to inclusion and exclusion criteria. Results: The analysis highlights transformational, inclusive, and innovative leadership styles as pivotal in fostering creativity, technological integration, and collaborative practices in the TVET area. Transformational leadership emerged as the most effective, emphasizing vision alignment and team empowerment. Inclusive and innovative leadership also demonstrated strong potential in enhancing institutional responsiveness to industry needs. Novelty: This study provides a comprehensive synthesis of the impact of leadership styles on innovation within TVET, addressing a critical gap in existing literature. It offers actionable insights for policymakers and practitioners to adopt leadership strategies that align educational outcomes with industry demands, ensuring institutional competitiveness and relevance.